Reserve System Design for Allocation of Scarce Medical Resources in a Pandemic - Pathak, Parag A.,Persad, Govind,Sönmez, Tayfun,Ünver, M. Utku (National Bureau of Economic Research, 2022)
The Covid-19 pandemic has brought renewed attention to rationing guidelines for scarce medical resources. This paper describes the benefits of using a reserve system over a priority system in operationalizing compromises between certain ethical goals. In the last two years, more than a dozen states and local jurisdictions have adopted reserve systems in initial phases of vaccine distribution. We highlight several design issues arising in some of these implementations
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Coronavirus; Impfung; Arzneimittel; Allokation; USA; Rationing; Licensing; Market Design; Government Policy; Regulation; Public Health